Outcome of locking compression plate fixation in the management of distal end femur fractures: one year hospital based study - Singh, Vishal; Gundavarapu, Avinash; Patel, Tejas; Sharma, Alokeshwar (International Journal of Research in Orthopaedics, 2021)
Background: Distal femur fractures make up 6 to 7% of all femur fractures. Various plating options for distal femur fracture are conventional buttress plates, fixed-angle devices, and locking plates. This study was planned to evaluate and explore locking compression plate fixation in distal end femur fractures which is expected to provide a stable fixation with minimum exposure, early mobilization, less complications and a better quality of life. Methods: The study was conducted as prospective clinical study in 20 skeletally mature patients with x-ray evidence of distal femur fracture fulfilling inclusion and exclusion criteria, operated with distal femur LCP plating. Patients were assessed radiologically and classified according to distal femur fracture classification and outcome graded as excellent, good, fair and poor based on Lysholm Knee Score. Results: Out of 15 excellent outcome cases, 3 cases were type A1 fracture, 1 case had type A3, 2 cases had type B1 and B2 each, 5 cases had type C2 and 2 cases had type C3 fracture. 1 case with good outcome was type C3. 1 case with fair outcome was type B2. While 3 cases with poor outcome were type A1, A2 and C3. Conclusions: The DF-LCP is an ideal implant to use for fractures of the distal femur. However, accurate positioning and fixation are required to produce satisfactory results. We recommend use of this implant in Type A and C, osteoporotic and periprosthetic fractures.